Technology as we do not know it: The extended practice of global software development. Issue 3 (July 2015) - Campagnolo, Gian Marco; Pollock, Neil; Williams, Robin
Abstract In this paper we propose an understanding of spatially and temporally extended practice. By introducing the notion of 'appresentation', we describe how global IT business actors make sense of matters that they cannot know directly. We make appresentation apparent by discussing how vendors take account of the needs of future customers and also of their current users of whom they have no direct knowledge. Based on long-term research into Information Technology market dynamics, we offer three examples of appresentation, used strategically by global IT vendors to link to sites and times that they have no direct experience of and examine how they extend their sense-making resources outwards from the local situation. The work that we call appresentation consists of a set of strategies including (i) preparation; (ii) user endowment and (iii) user segmentation. We contribute to existing perspectives on extended practice by describing how not knowing is used to produce knowledge that extends beyond the single site.